2021
DOI: 10.1007/s12217-020-09845-5
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Particle Structures in High-Prandtl-Number Liquid Bridges

Abstract: Clustering of small rigid spherical particles into particle accumulation structures (PAS) is studied numerically for a high-Prandtl-number (Pr = 68) thermocapillary liquid bridge. The one-way-coupling approach is used for calculation of the particle motion, modeling PAS as an attractor for a single particle. The attractor is created by dissipative forces acting on the particle near the boundary due to the finite size of the particle. These forces can dramatically deflect the particle trajectory from a fluid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The same accumulation measure has already been used in numerical and experimental studies [50,66]. For convenience we select the number of cells N = 4000 equal to the number of particles, thus N = N/N cells = 1, and use 10 × 40 × 10 cells in the radial, azimuthal, and axial directions, respectively.…”
Section: Monitoring the Temporal Evolution Of A Particle Ensemblementioning
confidence: 99%
See 1 more Smart Citation
“…The same accumulation measure has already been used in numerical and experimental studies [50,66]. For convenience we select the number of cells N = 4000 equal to the number of particles, thus N = N/N cells = 1, and use 10 × 40 × 10 cells in the radial, azimuthal, and axial directions, respectively.…”
Section: Monitoring the Temporal Evolution Of A Particle Ensemblementioning
confidence: 99%
“…While PAS has been studied extensively in lowand moderate-Prandtl-number liquid bridges on the ground, comprehensive experimental data and numerical results for Pr = 68, which is foreseen for JEREMI, are still lacking. Merely, a few hints about the existence of PAS in Pr = 68 thermocapillary liquid bridges have been detected during ISS experiments [49], while recent numerical studies [50,51] reported some preliminary findings on PAS formation. In the present study, we investigate PAS in thermocapillary liquid bridges for Pr = 68 to provide a numerical basis for future space experiments as well as to identify flow parameters and particle sizes for which PAS and FSCS are expected under zero gravity.…”
Section: Introductionmentioning
confidence: 99%